Work-associated irritable larynx syndrome. Issue 2 (April 2015) - Anderson, Jennifer A.
<x xml:space="preserve">Abstract</x> Purpose of review The purpose of this study is to review the relevant literature concerning work-associated irritable larynx syndrome (WILS), a hyperkinetic laryngeal disorder associated with occupational irritant exposure. Clinical symptoms are variable and include dysphonia, cough, dyspnoea and globus pharyngeus. WILS is a clinical diagnosis and can be difficult to differentiate from asthma. Treatment options for WILS include medical and behavioural therapy. Recent findings Laryngeal-centred upper airway symptoms secondary to airborne irritants have been documented in the literature under a variety of diagnostic labels, including WILS, vocal cord dysfunction (VCD), laryngeal hypersensitivity and laryngeal neuropathy and many others. The underlying pathophysiology is as yet poorly understood; however, the clinical scenario suggests a multifactorial nature to the disorder. More recent literature indicates that central neuronal plasticity, inflammatory processes and psychological factors are all likely contributors. Summary Possible mechanisms for WILS include central neuronal network plasticity after noxious exposure and/or viral infection, inflammation (i.e. reflux disease) and intrinsic patient factors such a psychological state. Treatment is individualized and frequently includes one or more of the following: environmental changes in the workplace, GERD therapy, behavioural/speech therapy, psychotherapy counselling and neural modifiers.